2017
DOI: 10.1111/acel.12590
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐aging drugs reduce hypothalamic inflammation in a sex‐specific manner

Abstract: SummaryAging leads to hypothalamic inflammation, but does so more slowly in mice whose lifespan has been extended by mutations that affect GH/IGF‐1 signals. Early‐life exposure to GH by injection, or to nutrient restriction in the first 3 weeks of life, also modulate both lifespan and the pace of hypothalamic inflammation. Three drugs extend lifespan of UM‐HET3 mice in a sex‐specific way: acarbose (ACA), 17‐α‐estradiol (17αE2), and nordihydroguaiaretic acid (NDGA), with more dramatic longevity increases in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 50 publications
5
63
1
Order By: Relevance
“…Accordingly, 4-weeks of benzene exposure resulted in a significant increase in GFAP + astrocytes in the different areas of the medial basal hypothalamus (MBH) such as the arcuate nucleus (ARC), the ventromedial (VMH), the dorsomedial (DM) hypothalamus as compared to control male mice ( Figure 3A and B). Consistent with previous studies [42,46,47], control females demonstrated a significantly lower number of immunostained GFAP + astrocytes in the MBH compared to control male mice ( Figure 3A and B).…”
Section: Benzene Induced Hypothalamic Inflammationsupporting
confidence: 92%
See 3 more Smart Citations
“…Accordingly, 4-weeks of benzene exposure resulted in a significant increase in GFAP + astrocytes in the different areas of the medial basal hypothalamus (MBH) such as the arcuate nucleus (ARC), the ventromedial (VMH), the dorsomedial (DM) hypothalamus as compared to control male mice ( Figure 3A and B). Consistent with previous studies [42,46,47], control females demonstrated a significantly lower number of immunostained GFAP + astrocytes in the MBH compared to control male mice ( Figure 3A and B).…”
Section: Benzene Induced Hypothalamic Inflammationsupporting
confidence: 92%
“…Similarly to metformin, ACA has beneficial effects on body weight, onset of diabetes and cardiovascular risk [36,37]. In mice, ACA effect replicates some aspects of diet or caloric restriction associated with increased lifespan [38][39][40][41], and with inhibition of age-associated hypothalamic inflammation in a sex-specific manner [42]. Our findings indicate that hypothalamic ER stress and hypothalamic inflammation might be critical for benzene diabetogenic effects, while ACA feeding, protects against benzene induced hypothalamic inflammation, ER stress and peripheral metabolic imbalance.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such sex‐specific effects on a metabolomic scale are consistent with the sex‐specific effects of 17aE2 on glucose tolerance (Garratt et al., 2017) and hypothalamic inflammation (Sadagurski, Cady & Miller, 2017). Furthermore, the response is not observed in males castrated prior to treatment onset, suggesting that this metabolic response to 17aE2 requires the presence of male gonadal hormones.…”
Section: Discussionmentioning
confidence: 99%